A comparison of chemical profile of various preparation methods of zingiber officinale rhizome - Mohd Sofi, Nabilah (2017)
Ginger is a member of Zingiberaceae family. Its scientific name is Zingiber officinale. Common name for ginger is "halia" in Malay ("Malaysian Herbal Monograph- Zingiber officinale Rose.,"). Its major compound is 6-gingerol. 6- Gingerol is dehydrated into 6-shogaol, which is a minor compound in ginger (Zingiber officinale Roscoe) and believe to be more potent than 6-gingerol. This study aims to compare chemical profile of fresh ginger rhizome using various preparation method: freeze-, boiling and oven drying at 60°C that are extracted with water and methanol. Water and methanol extract were used for Thin Layer Chromatography (TLC) performed on a silica gel 60 F254 as the stationary phase with toluene: ethyl acetate (3: 1 v/v) as mobile phase. A qualitative evaluation was performed by measuring the retention factor (Rr) of bands developed and characteristics of compounds in samples were observed under UV trans-illuminator at 254nm and 366nm wavelength. Chemical profile of fresh ginger rhizomes were different in each method of preparation. There was absence of 6-shogaol in boiled fresh ginger rhizome water extract, whereas 6-shogaol was present in freeze dried fresh ginger rhizome water extract. Fresh ginger rhizome oven dried at 60°C contained 6-shogaol compound same as oven dried rhizome because some of 6- gingerol compound were dehydrated into 6-shogaol. 6-Gingerol was present in all of the fresh ginger rhizome samples.